Draft Annual Plan 1993-94 Government of Tamil Nadu - Planning Commission (Planning Commission, 1992)
The outlay for the State’s Eighth Plan is Rs. 10,200 Crores at 1991-92 prices. The outlay for the year 1992-93 is Rs. 1,766.00 crores. The size of the Plan for the year 1993-94 has been discussed by the Chief Minister of Tamil Nadu with the Deputy Chairman. Union Planning Commission on 14th November 1992. After considering the needs of the State and the resources available, and to be mobilised, the total size of the Annual Plan for 1993-94 has been fixed at Rs. 2,101.00 cores. This represents a 20 per cent increase over the outlay for 1992-93.
State Planning Commission
State Planning Commission